Role of Runx2 in cell migratory ability of breast cancer cells. - Lim, Joleen Chooi-Hong. (2009)
Human breast cancers are known to preferentially metastasize to the skeletal sites and the osteolytic bone destruction associated with breast cancer skeletal metastases represents a serious and incurable clinical condition. However, the cellular understanding of breast cancer cells migrating to bone was limited. Findings have demonstrated that breast cancer cells express Runx2 (Cbfa/AML3, the Runt family of Transcription Factors), which was essential for bone formation and a regulator of skeletal homeostasis. In our present study, we explored the possible role of Runx2 function in affecting breast cancer cell phenotype via in vitro cell migration assay. A two-way approach was adopted in which Runx2 expression was silenced in metastatic breast cancer cell line, MDA-MB-231 or conversely, Runx2 expression was upregulated via transient transfection in non-metastatic breast cancer cell line, MCF7. Our experimental results demonstrated that the depletion of Runx2 expression in MDA-MB-231 cells resulted in a decrease in percent closure, cell migration distance, and cell migration rate; whereas over-expression of Runx2 in MCF7 cells enhanced its percent closure, cell migration distance and cell migration rate. In conclusion, Runx2 plays a role in enhancing cell migration of breast cancer cell lines.